Nickel-chromium-iron-aluminum alloy with good machinability, creep property and corrosion resistance and application of nickel-chromium-iron-aluminum alloy
A nickel-chromium-iron-aluminum alloy with optimized composition addresses the challenges of high-temperature corrosion and processing issues in solar tower systems by forming protective oxide layers, enhancing strength and longevity in nitrate salt environments.
Patent Information
- Application Number
- CN202411824032.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-03
- Filing Date
- 2020-12-04
- Publication Date
- 2025-03-18
AI Technical Summary
Existing high-temperature alloys used in solar tower systems face challenges with high-temperature corrosion and loss of strength due to high aluminum content, which affects their processing and longevity in environments with nitrate salt melts.
A nickel-chromium-iron-aluminum alloy with specific composition ranges for chromium, aluminum, iron, and other elements is developed to enhance stability, processability, and high-temperature strength, forming protective oxide layers and maintaining structural integrity.
The alloy demonstrates improved high-temperature strength, corrosion resistance, and processability, ensuring longer service life and efficiency in solar tower systems by forming stable oxide layers and maintaining structural integrity.
Smart Images

Figure CN119640094A_ABST
Abstract
Description
[0001] This divisional application is a divisional application based on the PCT invention patent application with application number 202080083974.4, whose application date is December 4, 2020 and which has entered the Chinese national phase, and whose invention name is "Nickel-chromium-iron-aluminum alloy with good machinability, creep performance and corrosion resistance and its application".
[0002] The present invention relates to a nickel-chromium-iron-aluminum wrought alloy having outstanding high temperature corrosion resistance, good creep strength and improved machinability.
[0003] Austenitic nickel-chromium-iron-aluminum alloys with different nickel, chromium and aluminum contents have long been used in furnace construction and in the chemical and petrochemical industries. Good high-temperature corrosion resistance and good high-temperature strength / creep strength are required for this use.
[0004] Nickel alloys with different nickel, chromium and aluminum contents are also widely used in solar tower power plants due to their properties. These devices consist of a mirror field (heliostat) arranged around a high tower. Through the mirrors, sunlight is concentrated on an absorber (solar receiver) mounted at the tip. The absorber consists of a tubular system in which a heat transfer medium is heated. The medium circulates in a loop with an intermediate storage tank. The thermal energy is converted into electrical energy in a secondary loop by means of a generator through a heat exchanger system. The heat transfer medium is mainly a salt mixture of sodium nitrate and potassium nitrate salt melts, which results in a maximum operating temperature of the salt of about 700°C, depending on the alloy used for the components (Kruizenga et al., Materials Corrosion of High Temperature Alloys Immersed in 600°C Binary Nitrate Salt, Sandia Report, SAND 2013-2526, 2013).
[0005] At temperatures above 700°C, the potassium nitrate salt melt will decompose significantly, which greatly increases the corrosion of metal pipes. Therefore, the maximum operating temperature is between 600°C and 700°C depending on the material. The commonly used materials in absorbers are 800H alloy (material number 1.4876, UNS N08810) or alloy 625 (material number 2.4856, UNS N06625) (see Table 1).
[0006] It is generally noted that the high temperature corrosion resistance of the alloys listed in Table 1 increases with increasing chromium content. Alloys containing aluminum form a chromium oxide layer (Cr2O3) with a more or less closed aluminum oxide layer (Al2O3) underneath. Small additions of highly oxygen-affinity elements, such as yttrium or cerium, increase the oxidation resistance. The chromium content is slowly consumed during use in the application area to form the protective layer. A higher chromium content therefore increases the service life of the material, since a higher chromium content of the element, which forms the protective layer, delays the point in time at which the chromium content falls below the critical limit and oxides other than Cr2O3, such as iron- and / or nickel-containing oxides, are formed. The high temperature corrosion resistance can be further increased by adding aluminum and / or silicon. From a certain minimum content, these elements form a closed layer below the chromium oxide layer and reduce the consumption of chromium.
[0007] The high temperature strength or creep strength at a given temperature is improved in particular by a high carbon content. However, high contents of mixed crystal strengthening elements such as chromium, aluminum, silicon, molybdenum and tungsten can also improve the high temperature strength. In the range of 500°C to 900°C, aluminum, titanium and / or niobium can be added to improve the strength by precipitation of γ'- and / or γ"-phases.
[0008] Table 1 lists examples of these alloys according to the prior art.
[0009] Alloy 602CA (N06025), Alloy 693 (N06693), Alloy 603 (N06603) or Alloy 214 (N07208) are known to have excellent corrosion resistance due to their high aluminum content exceeding 1.8% compared to Alloy 600 (N06600) or Alloy 601 (N06601). Due to its high aluminum content, Alloy 214 exhibits excellent corrosion resistance in a 60% sodium nitrate / 40% potassium nitrate salt melt (Kruizenga et al., Materials Corrosion of High Temperature Alloys Immersed in 600°C Binary Nitrate Salt, Sandia Report, SAND 2013-2526, 2013). At the same time, alloys 602CA (N06025), alloy 693 (N06693), alloy 603 (N06603) or alloy 214 (N07208) exhibit excellent high temperature strength or creep strength in the temperature range using nitrate melts due to their high carbon content or high aluminum content. Alloys 602CA (N06025) and alloy 603 (N06603) themselves still have excellent high temperature strength or creep strength at temperatures above 1000° C. However, for example, high aluminum contents can impair machinability, and the higher the aluminum content, the greater the impairment (for example alloy 693 (N06693) and alloy 214 (N07208)). The same is true for increased amounts of silicon, which forms low-melting intermetallic phases with nickel. In alloy 602CA (N06025) or alloy 603 (N06603), cold formability is particularly limited by the high proportion of primary carbides.
[0010] WO 2019 / 075177 A1 discloses a solar tower system comprising an absorber tube, a storage tank and a heat exchanger, all of which contain molten salt as a heat transfer medium at a temperature >650°C, wherein the disclosure includes that at least one component of the absorber tube, the storage tank and the heat exchanger is made of the following alloy, which contains, by mass percentage, 25-45% Ni, 12-32% Cr, 0.1-2.0% Nb, up to 4% Ta, up to 1% V, up to 2% Mn, up to 1.0% Al, up to 5% Mo, up to 5% W, up to 0.2% Ti, up to 2% Zr, up to 5% Co, up to 0.1% Y, up to 0.1% La, up to 0.1% Cs, up to 0.1% other rare earths, up to 0.20% C, up to 3% Si, 0.05-0.50% N, up to 0.02% boron and the remainder iron and impurities.
[0011] EP 0 508 058 A1 discloses an austenitic nickel-chromium-iron alloy composed, in mass percentage, of 0.12-0.3% C, 23-30% Cr, 8-11% Fe, 1.8-2.4% Al, 0.01-0.15% Y, 0.01-1.0% Ti, 0.01-1.0% Nb, 0.01-0.2% Zr, 0.001-0.015% Mg, 0.001-0.01% Ca, maximum 0.03% N, maximum 0.5% Si, maximum 0.25% Mn, maximum 0.02% P, maximum 0.01% S, the remainder Ni, including unavoidable impurities related to metallurgy.
[0012] US 4882125 B1 discloses a nickel alloy with a high chromium content, characterized by excellent resistance to sulfidation and oxidation at temperatures above 1093°C, excellent creep strength for more than 200 hours at temperatures above 983°C and a voltage of 2000PSI, good tensile strength and good elongation (both at room temperature and at elevated temperatures), which is composed of the following in weight percentage:
[0013] 27-35% Cr, 2.5-5% Al, 2.5-6% Fe, 0.5-2.5% Nb, up to 0.1% C, up to 1% Ti and Zr, up to 0.05% Ce, up to 0.05% Y, up to 1% Si, up to 1% Mn and the balance Ni.
[0014] EP 0 549 286 discloses a high temperature resistant nickel-chromium alloy comprising the following: 55-65% Ni, 19-25% Cr, 1-4.5% Al, 0.045-0.3% Y, 0.15-1% Ti, 0.005-0.5% C, 0.1-1.5% Si, 0-1% Mn and at least 0.005% in total of at least one of the elements of the group consisting of Mg, Ca, Ce, <0.5% in total of Mg+Ca, <1% Ce, 0.0001-0.1% B, 0-0.5% Zr, 0.0001-0.2% N, 0-10% Co, and the remainder of iron and impurities.
[0015] DE 600 04 737 T2 discloses a high-temperature-resistant nickel-based alloy containing the following: ≤0.1% C, 0.01-2% Si, ≤2% Mn, ≤0.005% S, 10-25% Cr, 2.1 to <4.5% Al, ≤0.055% N, a total of 0.001-1% of at least one of the elements B, Zr, Hf, wherein the elements may be present in the following contents: B ≤0.03%, Zr ≤0.2%, Hf <0.8%. 0.01-15% Mo, 0.01-9% W, where the total content of Mo+W can be 2.5-15%, 0-3% Ti, 0-0.01% Mg, 0-0.01% Ca, 0-10% Fe, 0-1% Nb, 0-1% V, 0-0.1% Y, 0-0.1% La, 0-0.01% Ce, 0-0.1% Nd, 0-5% Cu, 0-5% Co, and the balance is nickel. For Mo and W, the following formula must be satisfied:
[0016] 2.5 ≤ Mo + W ≤ 15 (1)
[0017] DE 10 2015 200881 A1 describes an austenitic steel tubular body for salt melts, in particular a solar receiver absorber tube with salt melts as heat carriers, or other pipelines for transporting salt melts, which comprises, based on weight:
[0018] 0% to 0.025% C, preferably 0.0095% to 0.024% C;
[0019] 0.05% to 0.16% N;
[0020] 2.4% to 2.6% Mo;
[0021] 0.4% to 0.7% Si;
[0022] 0.5% to 1.63% Mn;
[0023] 0% to 0.0375% P;
[0024] 0% to 0.0024% S;
[0025] 17.15% to 18.0% Cr;
[0026] 12.0% to 12.74% Ni;
[0027] 0.0025% to 0.0045% B;
[0028] The balance is iron and possible common impurities.
[0029] DE 102012002514 describes a nickel-chromium-aluminum-iron alloy which, in terms of mass percentage, contains 12 to 28% chromium, 1.8 to 3.0% aluminum, 1.0 to 15% iron, 0.01 to 0.5% silicon, 0.005 to 0.5% manganese, 0.01 to 0.20% yttrium, 0.02 to 0.60% titanium, 0.01 to 0.2% zirconium, 0.0002 to 0.05% magnesium, 0.0001 to 0.05% calcium, 0.0 3 to 0.11% carbon, 0.003 to 0.05% nitrogen, 0.0005 to 0.008% boron, 0.0001 to 0.010% oxygen, 0.001 to 0.030% phosphorus, up to 0.010% sulfur, up to 0.5% molybdenum, up to 0.5% tungsten, the balance nickel and common process-related impurities, where the following relationship must be satisfied: when PN>0, 7.7Cx*a<1.0 and a=PN, or when PN≤0, then a=0. Where x=(1.0Ti+1.06Zr) / (0.251Ti+0.132Zr) and PN=0.251Ti+0.132Zr-0.857N and Ti, Zr, N, C are the concentrations of the relevant elements in mass percentage.
[0030] DE 102012013437 B3 describes the use of a nickel-chromium-aluminum-iron alloy for producing seamless pipes, the alloy having, by mass percentage, >25% to 28% chromium, >2% to 3.0% aluminum, 1.0% to 11% iron, 0.01% to 0.2% silicon, 0.005% to 0.5% manganese, 0.01% to 0.20% yttrium, 0.02% to 0.60% titanium, 0.01% to 0.2% zirconium, 0.0002% to 0.05% magnesium, 0.0001% to 0.05% calcium, 0.03% to 0.11% carbon, 0.003% to 0.05% nitrogen, 0.0005% to 0.008% boron, 0.0001 to 0.010% oxygen, 0.001 to 0.030% phosphorus, up to 0.010% sulfur, up to 0.5% molybdenum, up to 0.5% tungsten, the remainder nickel and common process-related impurities, where the following relationship must be satisfied: 0<7.7Cx*a<1.0(2) and a=PN when PN>0(3a) or a=0 when PN≤0(3b) and x=(1.0Ti+1.06Zr) / (0.251Ti+0.132Zr)(3c), where PN=0.251Ti+0.132Zr-0.857N(4) and Ti, Zr, N, C are the concentrations of the relevant elements in mass percentage.
[0031] DE 102012011161 A1 describes a nickel-chromium-aluminum alloy having, by mass percentage, 24% to 33% chromium, 1.8% to 4.0% aluminum, 0.10% to 7.0% iron, 0.001% to 0.50% silicon, 0.005% to 2.0% manganese, 0.00% to 0.60% titanium, 0.0002% to 0.05% magnesium and / or calcium, respectively, 0.005% to 0.12% carbon, 0.001% to 0.050% nitrogen, 0.0001-0.020% oxygen, 0.001% up to 0.030% phosphorus, up to 0.010% sulfur, up to 2.0% molybdenum, up to 2.0% tungsten, the balance nickel and common process-related impurities, where the following relationship must be satisfied: Cr+Al≥28(2a) and Fp≤39.9 and (3a)Fp=Cr+0.272Fe+2.36Al+2.22Si+2.48Ti+0.374Mo+0.538W+11.8C(4a), where Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the relevant elements in mass percentage.
[0032] US 5,862,800 A discloses a solar tower power plant for bringing solar energy into molten salt, in which tubes of the same diameter and wall thickness are used, which are composed of alloy 625. The composition of alloy 625 is as follows: Cr 20-23%, Al≤0.4%, Fe≤5%, Si≤0.5%, Mn≤0.5%, Ti≤0.4%, C 0.03-0.1%, P≤0.02%, S≤0.015%, Mo 8-10%, Nb3.15-4.15%, and the balance of Ni (≥58%).
[0033] The object of the present invention is to design a nickel alloy with a sufficiently high chromium and aluminum content so that it has
[0034] Good phase stability,
[0035] Good processability,
[0036] Similar to Alloy 602CA (N06025), with good air corrosion resistance
[0037] and good high temperature strength / creep strength,
[0038] In order to provide it for other types of applications.
[0039] The object is achieved by a nickel-chromium-iron-aluminum alloy having, in percentage by mass, >17 to 33% chromium, 1.8 to <4.0% aluminum, 0.10 to 15.0% iron, 0.001 to 0.50% silicon, 0.001 to 2.0% manganese, 0.00 to 0.60% titanium, 0.0002 to 0.05% magnesium and / or calcium, respectively, 0.005 to 0.12% carbon, 0.001 to 0.050% nitrogen, 0.0001 to 0.020% oxygen, 0.001 to 0.030% phosphorus, a maximum of 0.010% sulfur, a maximum of 2.0% molybdenum, a maximum of 2.0% tungsten, a nickel balance of ≥50% nickel, and process-related impurities typical for use in solar tower power plants using nitrate melts as heat transfer medium, wherein the following relationship must be met:
[0040] Fp≤39.9 and (2a)
[0041] Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W-11.8*C(3a)
[0042] Wherein Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the relevant elements in mass %.
[0043] Among them, Cr, Fe, Al, Si, Ti, Nb, Cu, Mo, W and C are the concentrations of the relevant elements in mass %.
[0044] Advantageous further developments of the subject matter of the invention can be taken from the associated dependent claims.
[0045] Unless otherwise stated, all alloy content statements are in mass percent.
[0046] The distribution range of elemental chromium is between >17% and 33%, and the preferred range can be set as follows:
[0047] -> 18 to 33%
[0048] -20% to 33%
[0049] -22 to 33%
[0050] -24 to 33%
[0051] -25% to 33%
[0052] -26 to 33%
[0053] -27 to 32%
[0054] -28 to 32%
[0055] -> 28 to 32%
[0056] -29 to 31%
[0057] The aluminum content is between 1.8% and <4.0%, wherein here too, depending on the respective field of application of the alloy, the aluminum content can preferably be set as follows:
[0058] -1.8 to 3.8%
[0059] -1.8 to 3.2%
[0060] -2.0 to 3.2%
[0061] -2.0 to <3.0%
[0062] -2.0 to 2.8%
[0063] -2.2 to 2.8%
[0064] -2.2 to 2.6%
[0065] -2.5% to <4.0%
[0066] ->3.0-<4.0%
[0067] ->3.2-<4.0%
[0068] -> 3.2-3.8%
[0069] ->3.0-<3.5%
[0070] The iron content is between 0.1% and 15.0%, wherein, depending on the field of application, the preferred content can be set within the following distribution range:
[0071] -0.1-12.0%
[0072] -0.1-10.0%
[0073] -0.1-7.5%
[0074] -0.1-4.0%
[0075] -0.1-3.0%
[0076] -0.1-<2.5%
[0077] -0.1-2.0%
[0078] -0.1-<2.0%
[0079] -0.1-1.0%
[0080] -0.1-<1.0%
[0081] -1.0-15.0%
[0082] -1.25-15.0%
[0083] ->2.5-15.0%
[0084] ->4.0-15.0%
[0085] ->4.0-12.0%
[0086] ->7.0-15.0%
[0087] ->7.0-10.5%
[0088] -7.5-10.5%
[0089] The silicon content is between 0.001 and 0.50%. Preferably, Si can be arranged in the following distribution range in the alloy:
[0090] -0.001-<0,40%
[0091] -0.001-<0.25%
[0092] -0.001-0.20%
[0093] -0.001-<0.10%
[0094] -0.001-<0.05%
[0095] The same applies to the element manganese, which can be present in the alloy in an amount of 0.001% to 2.0%. Alternatively, the following distribution ranges are also conceivable:
[0096] -0.001-0.50%
[0097] -0001-<0.40%
[0098] -0.001-0.20%
[0099] -0.001-0.10%
[0100] -0.001-<0.05%
[0101] -0.005-<0.05%
[0102] The titanium content is between 0.00 and 0.60%. Preferably, Ti in the alloy can be arranged within the following distribution range:
[0103] -0.001-0.60%
[0104] -0.001-0.50%
[0105] -0.001-0.30%
[0106] -0.001-0.10%
[0107] -0.01-0.30%
[0108] -0.01-0.25%
[0109] -0.00-<0.02%
[0110] Magnesium and / or calcium are also contained in a content of 0.0002 to 0.05%. Preferably there is the possibility of adjusting these elements in the alloy as follows:
[0111] -0.0002-0.03%
[0112] -0.0002-0.02%
[0113] -0.0005-0.02%
[0114] The alloy contains 0.005 to 0.12% carbon. Preferably, this can be arranged in the following distribution range in the alloy:
[0115] -0.01-<0.12%
[0116] -0.005-0.10%
[0117] -0.005-<0.08%
[0118] -0.005-<0.05%
[0119] -0.01-0.03%
[0120] -0.01-<0.03%
[0121] -0.02-0.10%
[0122] -0.03-0.10%
[0123] The same applies to elemental nitrogen, which is contained in a content between 0.001 and 0.05%. Preferred contents can be given as follows:
[0124] -0.003-0.04%
[0125] The alloy also contains between 0.001 and 0.030% phosphorus. Preferred contents can be given as follows:
[0126] -0.001-0.020%
[0127] The alloy also contains between 0.0001 and 0.020% oxygen, and more particularly 0.0001 to 0.010%.
[0128] The elemental sulfur in the alloy is given by:
[0129] - Sulfur up to 0.010%
[0130] Molybdenum and tungsten are contained in the alloy alone or in combination, with the content being up to 2.0% respectively. The preferred content can be given as follows:
[0131] -Mo up to 1.0%
[0132] -W up to 1.0%
[0133] -Mo max <0.50%
[0134] -W < 0.50% at most
[0135] -Mo max <0.10%
[0136] -W < 0.10% at most
[0137] -Mo max <0.05%
[0138] -W <0.05% at most
[0139] Furthermore, to provide adequate phase stability, the following relationship must be satisfied:
[0140] Fp≤39,9 and (2a)
[0141] Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W-11.8*C(3a)
[0142] Wherein Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the relevant elements in mass %.
[0143] The preferred range can be set to:
[0144] Fp≤38.4(2b)
[0145] Fp≤36.6(2c)
[0146] The nickel content is greater than or equal to 50% or greater than 50%. Preferably, it can be set as follows:
[0147] - ≥55% or >55%
[0148] - ≥60% or >60%
[0149] - ≥65% or >65%
[0150] - ≥68% or >68%
[0151] Optionally, the content of the element yttrium in the alloy can be set to 0.001 to 0.20%. Preferably, Y can be set in the alloy within the following distribution range:
[0152] -0.001-0.15%
[0153] -0.001-0.10%
[0154] -0.001-0.08%
[0155] -0001-<0.045%
[0156] -0.01-<0.045%
[0157] Optionally, the content of element lanthanum in the alloy can be set to 0.001 to 0.20%. Preferably, La can be set in the alloy within the following distribution range:
[0158] -0.001-0.15%
[0159] -0.001-0.10%
[0160] -0.001-0.08%
[0161] -0.001-0.04%
[0162] -0.01-0.04%
[0163] Optionally, the content of element cerium in the alloy can be set to 0.001 to 0.20%. Preferably, Ce in the alloy can be set within the following distribution range:
[0164] -0.001-0.15%
[0165] -0.001-0.10%
[0166] -0.001-0.08%
[0167] -0.001-0.04%
[0168] -0.01-0.04%
[0169] Optionally, in the case of simultaneous addition of cerium and lanthanum, a cerium mixed metal (a mixture of about 50% Ce, about 25% La, about 15% Pr, about 5% Nd, Sm, Tb and Y) can also be used in an amount of 0.001 to 0.20%. Preferably, the cerium mixed metal can be arranged in the following distribution range in the alloy:
[0170] -0.001-0.15%
[0171] -0.001-0.10%
[0172] -0.001-0.08%
[0173] -0.001-0.04%
[0174] -0.01-0.04%
[0175] Optionally, the content of the element niobium in the alloy can be set between 0.00% and 1.10%. Preferably, the niobium in the alloy can be set within the following distribution range:
[0176] -0.001-<1.10%
[0177] -0.001-<0.70%
[0178] -0.001-<0.50%
[0179] -0.001-0.30%
[0180] -0.001-<0.30%
[0181] -0.001-<0.20%
[0182] -0.01-0.30%
[0183] -0.10-1.10%
[0184] -0.20-0.70%
[0185] If the alloy contains niobium, then an additional term must be added to equation (3a) for niobium as follows:
[0186] Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.374*Mo+0.538*W-11.8*C(3b)
[0187] Wherein Cr, Fe, Al, Si, Ti, Nb, Mo, W and C are the concentrations of the relevant elements in mass %.
[0188] Optionally, the zirconium content is between 0.001 and 0.20%. Preferably, zirconium may be arranged in the alloy within the following distribution range:
[0189] -0.001-0.15%
[0190] -0.001-<0.10%
[0191] -0.001-0.07%
[0192] -0.001-0.04%
[0193] -0.01-0.15%
[0194] -0.01-<0.10%
[0195] Optionally, the hafnium content is between 0.001 and 0.20%. Preferably, the hafnium in the alloy may be arranged within the following distribution range:
[0196] -0.001-0.15%
[0197] -0.001-<0.10%
[0198] -0.001-0.07%
[0199] -0.001-0.04%
[0200] -0.01-0.15%
[0201] -0.01-<0.10%
[0202] Optionally, 0.001 to 0.60% tantalum may also be present in the alloy.
[0203] Preferably, Ta in the alloy can be arranged within the following distribution range:
[0204] -0.001-0.60%
[0205] -0.001-0.50%
[0206] -0.001-0.30%
[0207] -0.001-0.10%
[0208] -0.001-<0.02%
[0209] -0.01-0.30%
[0210] -0.01-0.25%
[0211] Optionally, the element boron may be included in the alloy as follows:
[0212] -00001-0008%
[0213] Preferred contents can be given as follows:
[0214] -0.0005-0.008%
[0215] -0.0005-0.004%
[0216] In addition, the alloy may optionally contain 0.0% to 5.0% cobalt, which may also be limited as follows:
[0217] -0.001 to 5.0%
[0218] -0.01 to 5.0%
[0219] -0.01 to <5.0%
[0220] -0.01 to 2.0%
[0221] -0.1 to 2.0%
[0222] -0.1 to <2.0%
[0223] -0.001 to 0.5%
[0224] Furthermore, up to 0.5% copper may be present in the alloy.
[0225] Copper content may also be limited as follows:
[0226] - Up to 0.20%
[0227] - Up to 0.10%
[0228] - Up to 0.05%
[0229] -<0.05%
[0230] - Up to 0.015%
[0231] -<0.015%
[0232] If the alloy contains copper, equation (3a) must be supplemented with an additional term for copper as follows:
[0233] Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.477*Cu+0.374*Mo+0.538*W-11.8*C(3c)
[0234] Among them, Cr, Fe, Al, Si, Ti, Cu, Mo, W and C are the concentrations of the relevant elements in mass %.
[0235] If the alloy contains niobium and copper, equation (3a) must be supplemented by adding a term for niobium and a term for copper as follows:
[0236] Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.477*Cu+0.374*Mo+0.538*W-11.8*C(3d)
[0237] Among them, Cr, Fe, Al, Si, Ti, Nb, Cu, Mo, W and C are the concentrations of the relevant elements in mass %.
[0238] Furthermore, up to 0.5% vanadium may be present in the alloy.
[0239] The vanadium content may also be limited as follows:
[0240] - Up to 0.20%
[0241] - Up to 0.10%
[0242] - Up to 0.05%
[0243] Finally for impurities, the elements lead, zinc and tin can be given as follows:
[0244] Pb max 0.002%
[0245] Zn max 0.002%
[0246] Sn: 0.002% at most.
[0247] Furthermore, the following relationship, which can exhibit particularly good processability, can be selectively satisfied:
[0248] Fa≤60 and (4a)
[0249] Fa=Cr+20.4*Ti+201*C(5a)
[0250] Wherein Cr, Ti and C are the concentrations of the relevant elements in mass %.
[0251] The preferred range can be set to:
[0252] Fa≤54(4b)
[0253] If the alloy contains niobium, then a supplementary term must be added to equation (5a) using niobium:
[0254] Fa=Cr+6.15*Nb+20.4*Ti+201*C(5b)
[0255] Where Cr, Nb, Ti and C are the concentrations of the relevant elements in mass %.
[0256] In addition, the following relationship can be selectively satisfied for high temperature strength or creep strength, which exhibits particularly good performance:
[0257] Fk ≥ 47 and (6a)
[0258] Fk=Cr+19*Ti+10.2*Al+12.5*Si+98*C(7a)
[0259] Wherein Cr, Ti, Al, Si and C are the concentrations of the relevant elements in mass %.
[0260] The preferred range can be set to:
[0261] Fk≥49(6b)
[0262] Fk≥53(6c)
[0263] If the alloy contains niobium and / or boron, equation (7a) must be supplemented with the niobium and / or boron addition terms as follows:
[0264] Fk=Cr+19*Ti+34.3*Nb+10.2*Al+12.5*Si+98*C+2245*B
[0265] (7b)
[0266] Wherein Cr, Ti, Nb, Al, Si, C and B are the concentrations of the relevant elements in mass %.
[0267] The alloy according to the invention is preferably open-melted and then processed in a VOD (vacuum oxygen decarburization) or VLF (vacuum ladle furnace) plant. However, melting and casting in vacuum (VIM) is also possible. After casting into blocks or as continuous casting, the alloy is optionally annealed at a temperature between 900° C. and 1270° C. for 0.1 to 100 hours in the desired semi-finished form and then hot-formed, optionally with intermediate annealing between 900° C. and 1270° C. for 0.05 hours to 100 hours. The surface of the material can optionally (also multiple times) be chemically and / or mechanically removed during and / or at the end for cleaning. After the hot forming is completed, cold forming with a forming degree of up to 98% can be optionally carried out to form the desired semi-finished product, and an intermediate annealing is optionally carried out between 700°C and 1250°C for 0.1 minutes to 70 hours, optionally under a protective gas, such as argon or hydrogen, and then cooled in air, in a moving annealing atmosphere or in a water bath. Then, solution annealing is carried out in a temperature range of 700°C to 1250°C for 0.1 minutes to 70 hours, optionally under a protective gas, such as argon or hydrogen, and then cooled in air, in a moving annealing atmosphere or in a water bath. Afterwards, if necessary, solution annealing is carried out in a temperature range of 700°C to 1250°C for 0.1 minutes to 70 hours. Optionally under a protective gas, such as argon or hydrogen, and then cooled in air, a moving annealing atmosphere or a water bath. Optionally, chemical and / or mechanical cleaning of the material surface can be carried out during and / or after the last annealing.
[0268] The alloy according to the invention can be produced and used well in the product form of strips, sheets, bars, wires, longitudinally welded tubes and seamless tubes.
[0269] These product forms are produced with an average grain size of 5 μm to 600 μm. The preferred range is between 20 μm and 200 μm.
[0270] The alloy according to the invention is preferably used in solar tower power plants using nitrate melts as heat transfer medium.
[0271] It can be used for all parts that come into contact with molten salt.
[0272] It can be used in particular in absorbers (solar receivers) in towers of solar power plants and / or in heat exchangers and / or storage and / or transport pipes for power generation circuits (eg via steam turbines).
[0273] The nitrate salt may preferably be a mixture of sodium nitrate and potassium nitrate salts.
[0274] The mixture may preferably consist of the following composition:
[0275] -50-70% sodium nitrate and 50-30% potassium nitrate
[0276] -55-65% sodium nitrate and 45-35% potassium nitrate
[0277] -58-62% sodium nitrate and 42-38% potassium nitrate
[0278] Alternatively, a mixture of sodium nitrate, potassium nitrate and sodium nitride may be used.
[0279] If desired, the salt mixture can also be used under a pure CO2 atmosphere.
[0280] The maximum operating temperature is 800°C. The following restrictions may apply:
[0281] -Maximum 750℃
[0282] -Maximum 700℃
[0283] -Maximum 680℃
[0284] -Maximum 650℃
[0285] -<650℃
[0286] -Maximum 620℃
[0287] -Maximum 600℃
[0288] -<600℃
[0289] Tests performed
[0290] Phase stability
[0291] The equilibrium phases of the different alloy variants were calculated using the JMatPro program from Thermotech. The database of nickel-based alloys TTNI7 from Thermotech was used as the data basis for the calculations.
[0292] According to DIN EN ISO 6892-1, the formability is determined by a tensile test at room temperature. The tensile limit Rp is determined in this way. 0.2 , tensile strength R m And the elongation A until fracture. On the fractured sample, the original measurement distance L0 and the measured length L after fracture are u The elongation determines the elongation A:
[0293] A=(L U -L0) / L0 100%=ΔL / L0 100%
[0294] Depending on the measuring length, the elongation at break has the following indications:
[0295] For example, for A5, the measuring length L0=5·d0 and d0=the initial diameter of the circular specimen.
[0296] The test was conducted on a circular sample with a diameter of 6 mm and a measuring length L0 of 30 mm within the measuring range. The sample was taken transversely along the forming direction of the semi-finished product. The forming speed was R p0.2 is 10MPa / s and at R m 6.7 10 -3 1 / s(40% / min).
[0297] The measured value of the elongation A in a room temperature tensile test can be taken as a measure of plasticity. A well processable material should have an elongation of at least 50%.
[0298] The elevated temperature strength is determined in a hot tensile test according to DIN EN ISO 6892-2. In this case, similar to the room temperature tensile test (DIN EN ISO 6892-1), the tensile limit R is determined. p0.2 , tensile strength R m and the elongation A until break.
[0299] The test was conducted on a circular sample with a diameter of 6 mm and an initial measuring length L0 of 30 mm within the measuring range. The samples were taken transversely along the forming direction of the semi-finished product. The forming speed was R p0.2 8.33 10 -5 1 / s (0.5% / min) and R m 8.33 10 -4 1 / s (5% / min) (DIN EN ISO 6892-2).
[0300] The sample is mounted in the tensile tester at room temperature and heated to the required temperature without applying tension. After reaching the test temperature, temperature compensation is performed for one hour (600°C) or two hours (700°C to 1100°C). After this, the sample is loaded with tension to maintain the required extension rate and the test is started.
[0301] The creep strength of a material can be improved with the increase of high temperature strength. Therefore, high temperature strength is also used to evaluate the creep strength of different materials.
[0302] The corrosion resistance at high temperature is determined by oxidation tests in air at 1000°C, where the test is interrupted every 96 hours and the mass change of the sample due to oxidation is determined. During the experiment, the sample is placed in a ceramic crucible so that any flaked oxide can be collected as appropriate, and the mass of the flaked oxide can therefore be determined. The sum of the mass change of the sample (net mass change) and the mass of the flaked oxide is the total mass change of the sample. The specific mass change is the mass change associated with the sample surface. The following is expressed in m Netto Represents the specific net mass change, m Brutto Indicates the change in total mass, m spall Indicates the specific mass change of the exfoliated oxide. The test was carried out on samples with a thickness of about 5 mm. Three samples were removed from each batch, and the value given is the average of these three samples.
[0303] Property Description
[0304] -Corrosion resistance in salt melts
[0305] In Kruizenga et al. (2013, Corrosion of high-temperature alloys immersed in binary nitrates at 600°C), in particular, nickel alloy 625 (N06625), alloy 120 (N08120), alloy 230 (N02230), alloy 242 (N10242), alloy 214 (N07208) (Table 1) were studied for their corrosion resistance at 600°C in a salt melt consisting of 60% sodium nitrate salt and 40% potassium nitrate salt with air circulation. The analysis of the alloys used is shown in Table 2. After the test, the weight of the oxide layer was determined by removing the oxide layer from the metal surface and weighing the sample before, after and after the test. This determined the weight loss relative to the sample surface before the test (descaling loss).
[0306] Table 3 shows the corrosion rate after 3000 hours: once in mg / cm 2The corrosion rate is calculated as the descaling loss in μm / year and as the metal loss in μm / year. The lowest corrosion rate is that of alloy 214 with an aluminum content of 4.5% at a corrosion rate of 5.7 μm / year, followed by alloy 224 with an aluminum content of 3.8% at a corrosion rate of 8.3 μm / year. All other nickel alloys tested (alloy 625, alloy 120, alloy 242 and alloy 230) have a significantly higher corrosion rate of 16.8 μm / year and a higher aluminum content of less than 0.5%. Alloys 214 and 224 form an aluminum oxide layer, which provides good protection against nitrate melts. If the aluminum content is too low, such as in alloys 625, alloy 120, alloy 242 and alloy 230, no aluminum oxide layer is formed, resulting in an increased corrosion rate. It is therefore advantageous that the alloy used in nitrate melts has a sufficiently large aluminum content to form a closed aluminum oxide layer.
[0307] In addition to excellent corrosion resistance in nitrate melts, the alloy according to the invention has the following properties:
[0308] Good phase stability
[0309] Good processability
[0310] Similar to 602CA alloy (N06025), it has good air corrosion resistance
[0311] Good high temperature strength / creep strength
[0312] Phase stability
[0313] In nickel-chromium-iron-aluminum systems with additions of Ti and / or Nb, various brittle TCP (topologically close packed) phases such as Laves phases, Sigma phases or μ-phases or brittle h-phases or ε-phases may form, depending on the alloy content (see, for example, Ralf Bürgel, Handbook of High Temperature Materials Technology (Handbuch der Hochtemperaturewerkstofftechnik), 3rd edition, Vieweg Verlag, Wiesbaden, 2006, pages 370-374). For example, the calculation of the equilibrium phase proportions of N06690 of batch 111389 as a function of temperature (typical composition see Table 4) shows computationally that at 720°C (T s BCC ) forms α-chromium ( Figure 1 The formation of this phase is very difficult because it is analytically very different from the base material. However, if the solvus temperature T s BCCVery high, it certainly appears, as described in E. "Slevolden, JZ Albertsen. U. Fink, "Tjeldbergodden Methanol Plant: Metal Dusting Investigations," Corrosion / 2011, Paper No. 11144 (Houston, TX: NACE 2011), p. 15" for a variant of Alloy 693 (UNS 06693). For Alloy 3 or Alloy 10 of Table 4, Figure 2 and Figure 3 The phase diagram of alloy 693 variant (from US 4,88,125 Table 1) is shown. This phase is brittle and thus leads to unnecessary brittleness of the material. The formation temperature T of alloy 3 s BCC is 1079°C, and the formation temperature of alloy 10 is 939°C. In "E. Slevolden, JZ Albertsen. U. Fink, Tjeldbergodden Methanol Plant: Metal Dusting Investigations," Corrosion / 2011, Paper No. 11144 (Houston, TX: NACE 2011), page 15", the exact analysis of the alloy in the case of α-chromium (BCC phase) is not described, but it can be assumed that in the example of alloy 693 given in Table 4, the highest solvus temperature T is calculated. s BCC In the analysis of alloys such as Alloy 10, α-chromium can be formed. In the corrected analysis in “E. Slevolden, JZ Albertsen. U. Fink, Tjeldbergodden Methanol Plant: Metal Dusting Investigations,” Corrosion / 2011, Paper No. 11144 (Houston, TX: NACE 2011), page 15” (using a reduced solvent temperature T s BCC ) α-chromium is only detected near the surface. In order to avoid the appearance of this brittle phase, in the alloy of the present invention, the solvus temperature T s BCC Less than or equal to 939 ° C, which corresponds to the lowest solvus temperature T in the example of alloy 693 in Table 4 s BCC (Extracted from Table 1 of US 4,88,125).
[0314] This is especially true if:
[0315] Fp≤39.9 and (2a)
[0316] Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.477*Cu+0.374*Mo+0.538*W-11.8*C(3d)
[0317] Where Cr, Al, Fe, Si, Ti, Nb, Cu, Mo, W and C are the concentrations of the relevant elements in mass %. Table 4 of the alloys according to the prior art shows that the Fp of alloys 8, 3 and 2 is greater than 39.9, and the Fp of alloy 10 is exactly 39.9. s BCC For all other alloys below 939°C, Fp ≤ 39.9.
[0318] -Processability
[0319] For example, formability is considered here for processability.
[0320] Alloys can be hardened by various mechanisms so that they have high temperature strength or creep strength. Therefore, the addition of another element to the alloy, the distribution of which depends on the element, leads to a more or less increased strength (mixed crystal hardening). A more effective method is to increase the strength by fine particles or precipitation (particle hardening). For example, the γ′-phase formed by adding aluminum and other elements (such as Ti) to nickel alloys or carbides formed by adding carbon to chromium-containing nickel alloys (see Ralf Bürgel, Handbook of High Temperature Materials Technology, 3rd edition, Vieweg Publishing House, Wiesbaden, 2006, pages 358-369).
[0321] An increase in the content of γ′-phase forming elements or C content increases the high temperature strength but increasingly impairs the formability, even in the solution annealed state.
[0322] For a very good formable material, the aim is an elongation A5 of 50% or more, at least 45% or more in a tensile test at room temperature.
[0323] This is achieved in particular when the following relationship is satisfied between the carbide-forming elements Cr, Nb, Ti and C:
[0324] Fa≤60 and (4a)
[0325] Fa=Cr+6.15*Nb+20.4*Ti+201*C(5b)
[0326] Where Cr, Nb, Ti and C are the concentrations of the relevant elements in mass %.
[0327] -High temperature strength / creep strength
[0328] At the same time, the tensile limit or tensile strength at higher temperatures should at least reach the value of alloy 601 (see Table 6).
[0329] 600℃: tensile limit Rp0.2 >150Mpa; tensile strength Rm >500MPa(8a,8b)
[0330] 800℃: tensile limit Rp0,2 >130Mpa; tensile strength Rm >135MPa(8c,8d)
[0331] It is desirable that the tensile limit or tensile strength be within the tensile strength range of Alloy 602CA (see Table 6). At least three of the following four relationships should be met:
[0332] 600℃: tensile limit Rp0.2 >250MPa; tensile strength Rm >570Mpa(9a,9b)
[0333] 800℃: tensile limit Rp0.2 >180MPa; tensile strength Rm >190Mpa(9c,9d)
[0334] Requirements 8a, 8b, 8c and 8d are particularly met when the following relationships between the main hardening elements are met:
[0335] Fk ≥ 47 and (6a)
[0336] Fk=Cr+19*Ti+34.3*Nb+10.2*Al+12.5*Si+98*C+2245*B
[0337] (7b)
[0338] Wherein Cr, Ti, Nb, Al, Si, C and B are the concentrations of the relevant elements in mass %.
[0339] - Air corrosion resistance:
[0340] The alloy according to the invention should have good atmospheric corrosion resistance similar to that of alloy 602CA (N06025). BRIEF DESCRIPTION OF THE DRAWINGS
[0341] Figure 1 : Taking the typical batch 111389 as an example (Table 5a and b), the phase ratio in thermodynamic equilibrium is expressed as mass percentage Function of temperature for Alloy 690 (N06690). Calculated using JmatPro.
[0342] Figure 2 : Taking alloy 3 in Table 4 as an example, the phase ratio in thermodynamic equilibrium is the same as that of alloy 693 in terms of mass percentage. (N06693) as a function of temperature. Calculated using JmatPro.
[0343] Figure 3 : Taking alloy 10 in Table 4 as an example, the phase ratio in thermodynamic equilibrium is the same as that of alloy 693 in terms of mass percentage. (N06693) as a function of temperature. Calculated using JmatPro. Example
[0344] -Production:
[0345] Tables 5a and 5b show the analysis of laboratory scale melting batches and some prior art large scale melting batches for comparison of 602CA alloy (N06025), 690 alloy (N06690), 601 alloy (N06601). Batches according to the prior art are marked with T, and batches according to the present invention are marked with E. Batches from laboratory scale melting are marked with L, and batches from large scale melting are marked with G.
[0346] The alloy blocks from Table 5a and Table 5b, which were vacuum melted on a laboratory scale, were annealed between 900° C. and 1270° C. for 8 hours and hot rolled to a final thickness of 13 mm or 6 mm by means of hot rolling and further intermediate annealing between 900° C. and 1270° C. for 0.1 to 1 hour. The resulting sheets were solution annealed between 900° C. and 1270° C. for 1 hour. The samples required for the measurements were made from these sheets.
[0347] In the case of large-scale melting of alloys, samples are taken from sheets of suitable thickness manufactured in the factory during large-scale production. Samples required for measurement are made from these sheets.
[0348] The grain size for all alloy variants is typically between 70 and 505 μm.
[0349] For the sample batches in Tables 5a and b, the following properties were compared:
[0350] -Corrosion resistance in nitrate melts
[0351] - Phase stability
[0352] -Formability based on room temperature tensile test
[0353] -High temperature strength / creep strength by hot tensile test
[0354] -Corrosion resistance to air by oxidation test
[0355] -Corrosion resistance in nitrate melts:
[0356] In the case of the laboratory-scale smelting batches 2301, 250129 to 250138 and 250147 to 250149, as well as batches 250164, 250311 and 250526, the aluminum content is greater than or equal to 1.8%. This aluminum content is large enough to form a closed aluminum oxide layer under the chromium oxide layer. Therefore, they meet the requirements for corrosion resistance in salt melts.
[0357] -Phase stability:
[0358] Therefore, the solvus temperature T was calculated for the alloys selected according to the prior art in Table 4 and for all laboratory batches (Tables 5a and 5b) and entered in Tables 4 and 5a. s BCC Calculate the phase diagram of the selected alloy. For the compositions in Tables 4 and 5a and b, the value of Fp is also calculated according to Formula 3d. The larger the Fp, the higher the solvus temperature T s BCC The larger the solid solution temperature T s BCC All examples of N06693 above Alloy 10 have Fp>39.9. Therefore, requiring Fp≤39.9 (Equation 2a) is a good criterion for obtaining adequate phase stability in the alloy. All laboratory batches in Tables 5a and b meet the Fp≤39.9 criterion.
[0359] -Formability (processability):
[0360] Table 6 shows the tensile limit R at room temperature (RT) and 600 °C. p0.2 , tensile strength R m and elongation A5, tensile strength R at 800°C m The values of Fa and Fk are also shown.
[0361] In Table 6, the elongation A5 of alloy sample batches 156817 and 160483 prepared according to the prior art alloy 602CA at room temperature is relatively small, 36 and 42%, respectively, which is lower than the requirement for good formability. Fa is greater than 60 and is thus above the range characterizing good formability. The elongation of all alloys of the present invention (E) is greater than 50%. They meet the requirements. For all alloys according to the present invention, Fa is less than 60. Therefore, they are in the range with good formability. When Fa is relatively small, the elongation is particularly high.
[0362] -High temperature strength / creep strength:
[0363] In Table 6, the alloy sample batch 156656 according to the prior art alloy 601 is an example of the minimum requirements for tensile limit and tensile strength at 600°C and 800°C. In contrast, the sample batches 156817 and 160483 according to the prior art alloy 602CA are examples of very good tensile limit and tensile strength values at 600°C and 800°C. Alloy 601 represents a material that meets the minimum requirements for high temperature strength or high temperature strength, which is described in relations 8a to 8d. Alloy 602CA represents a material with excellent high temperature strength or creep strength, which is described in relations 9a to 9d. The Fk values of both alloys are significantly higher than 47, and the Fk value of alloy 602CA is also significantly higher than that of alloy 601, which reflects the increase in the strength value of alloy 602CA. The alloys according to the present invention (E) all show tensile limits and tensile strengths within or far above the range of 601 alloy at 600°C and 800°C, and thus meet relations 8a to 8d. They are within the value range of alloy 602CA and, with the exception of batches 250526 and 250311, also meet the ideal requirements, i.e., 3 of the 4 relations 9a to 9d. Moreover, for all alloys according to the invention in the examples in Table 6, Fk is greater than 47 or greater than 54 and is thus in the range characterized by good high temperature strength or creep strength. Among the laboratory batches not according to the invention, batches 2297 and 2300 are examples where relations 8a to 8d are not met and where Fk is less than 47.
[0364] - Air corrosion resistance:
[0365] Table 7 shows the specific mass change after oxidation tests at 1100°C in air after 11 cycles of 96 hours (i.e. a total of 1056 hours). Table 7 shows the specific total mass change, specific net mass change and specific mass change of the oxides peeled off after 1056 hours. Sample batches of alloys 601 and alloy 690 according to the prior art show a significantly higher total mass change than alloy 602CA, where the total mass change of alloy 601 is again significantly greater than the total mass change of alloy 690. Both form a chromium oxide layer that grows faster than the aluminum oxide layer. Alloy 601 still contains about 1.3% aluminum. The aluminum content is too low to form a partially closed aluminum oxide layer, which is why aluminum is oxidized inside the metal material below the oxide layer (internal oxidation). This leads to an increase in mass compared to alloy 690. Alloy 602CA has about 2.3% aluminum. As a result, the alloy is able to form a closed aluminum oxide layer below the chromium oxide layer. This significantly reduces the growth of the oxide layer and therefore also reduces the increase in specific mass. All alloys (E) according to the invention contain at least 2% aluminum and therefore have a similar low or lower total mass gain as alloy 602CA. All alloys according to the invention show flaking similar to the sample batch of alloy 602CA within the measurement accuracy, while alloy 601 and alloy 690 show large flaking.
[0366] Therefore, the required definitions for alloy "E" according to the present invention can be specifically stated as follows:
[0367] Too low a chromium content means that when the alloy is used in a corrosive environment, the chromium concentration quickly drops below a critical limit, so that a closed chromium oxide layer can no longer form. Therefore, a chromium content of more than 17% is a lower limit. Too high a chromium content impairs the phase stability of the alloy, especially in the case of high aluminum contents of ≥ 1.8%. Therefore, 33% chromium is considered an upper limit.
[0368] The formation of an aluminum oxide layer beneath the chromium oxide layer reduces the oxidation rate. Below 1.8% aluminum, the aluminum oxide layer is too crack-filled to fully function. Too high an aluminum content will affect the machinability of the alloy. Therefore, an aluminum content <4.0% constitutes an upper limit.
[0369] The cost of the alloy increases with decreasing iron content. Below 0.1%, the costs increase disproportionately, since special raw materials must be used. Therefore, for cost reasons, 0.1% of iron should be considered a lower limit. Increasing the iron content reduces the phase stability (formation of brittle phases), especially in the case of higher chromium and aluminum contents. Therefore, 15% of iron is a reasonable upper limit to ensure the phase stability of the alloy according to the invention.
[0370] Silicon is required in the production of the alloy. Therefore, a minimum content of 0.001% is necessary. Excessive contents can in turn impair processability and phase stability, especially in the case of high aluminum and chromium contents. Therefore, the silicon content is limited to 0.50%.
[0371] A minimum level of 0.001% manganese is necessary to improve machinability. Manganese is limited to 2.0% because this element reduces oxidation resistance.
[0372] Titanium improves high temperature resistance. From 0.60%, oxidation behavior deteriorates, which is why 0.60% is the maximum.
[0373] Even low magnesium and / or calcium contents improve machinability by binding sulfur, thus avoiding the formation of low-melting nickel-sulfur eutectics. Therefore, a minimum magnesium and / or calcium content of 0.0002% is required. In the case of excessively high contents, intermetallic nickel-magnesium phases or nickel-calcium phases occur, which again significantly deteriorate machinability. Therefore, the magnesium content and / or calcium content is limited to a maximum of 0.05%.
[0374] A minimum content of 0.005% carbon is necessary for good creep strength. The maximum carbon content is limited to 0.12% since above this content the element reduces the machinability due to excessive formation of primary carbides.
[0375] A minimum nitrogen content of 0.001% is required to improve the machinability of the material. The maximum nitrogen content is limited to 0.05% due to the formation of coarse carbonitrides which reduce machinability.
[0376] The oxygen content must be less than or equal to 0.020% to allow for the alloy's manufacturability. Too low an oxygen content will increase costs. Therefore, the oxygen content is ≥ 0.0001%.
[0377] The phosphorus content should be less than or equal to 0.030% because this interface activating element will impair oxidation resistance. Too low a phosphorus content will increase costs. Therefore, the phosphorus content is ≥ 0.001%.
[0378] The sulfur content should be set as low as possible, since this interface-activating element impairs the oxidation resistance. A maximum of 0.010% sulfur is therefore established.
[0379] Molybdenum is limited to a maximum of 2.0% because this element reduces oxidation resistance.
[0380] Tungsten is limited to a maximum of 2.0% as this element also reduces oxidation resistance.
[0381] Nickel is a residual element. Too low a nickel content will reduce phase stability, especially when the chromium content is high. Therefore, nickel must be greater than or equal to 50%.
[0382] Furthermore, in order to provide adequate phase stability, the following relationship must be satisfied:
[0383] Fp≤39.9 and (2a)
[0384] Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W-11.8*C(3a)
[0385] Where Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the relevant elements in mass %. The previous text explains in detail the limitations of Fp and other elements that may be included.
[0386] If necessary, oxygen-philic elements such as yttrium, lanthanum, cerium, and cerium mixed metals can be added to further improve oxidation resistance. These elements are incorporated into the oxide layer and block the diffusion path of oxygen at the grain boundaries.
[0387] A minimum content of 0.001% yttrium is necessary to obtain the oxidation resistance enhancing effect of yttrium. For cost reasons, the upper limit is set at 0.20%.
[0388] A minimum content of 0.001% lanthanum is necessary to obtain the oxidation resistance enhancing effect of lanthanum. For cost reasons, the upper limit is set at 0.20%.
[0389] A minimum content of 0.001% cerium is necessary to obtain the antioxidant enhancing effect of cerium. For cost reasons, the upper limit is set at 0.20%.
[0390] A minimum content of 0.001% cerium mixed metal is necessary to obtain the oxidation resistance enhancing effect of the cerium mixed metal. For cost reasons, the upper limit is set at 0.20%.
[0391] Niobium can be added if necessary, as it also increases high temperature resistance. Higher levels increase costs significantly. Therefore, the upper limit is determined to be 1.10%.
[0392] If desired, the alloy may also contain tantalum, as it also improves high temperature resistance and oxidation resistance. Higher levels increase costs substantially. Therefore, the upper limit is determined to be 0.60%. A minimum content of 0.001% is required to achieve the effect.
[0393] If desired, the alloy may also contain zirconium. A minimum content of 0.001% zirconium is necessary to obtain the high temperature strength and oxidation resistance enhancement effects of zirconium. For cost reasons, the upper limit of zirconium is set at 0.20%.
[0394] If desired, the alloy may also contain hafnium. A minimum content of 0.001% hafnium is necessary to obtain the high temperature strength and oxidation resistance enhancing effects of hafnium. For cost reasons, the upper limit of hafnium is set at 0.20%.
[0395] Boron can be added to the alloy if necessary, since it improves creep strength. Therefore, it should be present in a content of at least 0.0001%. At the same time, this interface activating element reduces oxidation resistance. Therefore, a maximum of 0.008% boron is determined.
[0396] The cobalt content of this alloy can be up to 5.0%. Higher contents will significantly reduce oxidation resistance.
[0397] Copper is limited to a maximum of 0.5% as this element reduces oxidation resistance.
[0398] Vanadium is limited to a maximum of 0.5% since this element reduces oxidation resistance.
[0399] Lead is limited to a maximum of 0.002% as this element reduces oxidation resistance. The same is true for zinc and tin.
[0400] Furthermore, the following relationship for the carbide-forming elements chromium, titanium and carbon can optionally be met, which describes particularly good machinability:
[0401] Fa≤60 and (4a)
[0402] Fa=Cr+20.4*Ti+201*C(5a)
[0403] Where Cr, Ti and C are the concentrations of the relevant elements in mass %. The limitation of Fa and the possible inclusion of other elements are explained in detail above.
[0404] Furthermore, the following relationship between the strength-increasing elements can optionally be satisfied, which describes particularly good high-temperature strength or creep strength:
[0405] Fk ≥ 47 and (6a)
[0406] Fk=Cr+19*Ti+10.2*Al+12.5*Si+98*C(7a)
[0407] Where Cr, Ti, Al, Si and C are the concentrations of the relevant elements in mass %. The limitation of Fa and the possible inclusion of other elements are explained in detail above.
[0408]
[0409]
[0410]
[0411]
[0412]
[0413]
[0414]
[0415]
[0416] Technical Solution
[0417] 1. Nickel-chromium-iron-aluminium alloys having, in % by mass, >17 to 33% chromium, 1.8 to <4.0% aluminium, 0.10 to 15.0% iron, 0.001 to 0.50% silicon, 0.001 to 2.0% manganese, 0.00 to 0.60% titanium, 0.0002 to 0.05% magnesium and / or calcium, respectively, 0.005 to 0.12% carbon, 0.001 to 0.050% nitrogen, 0.0001 to 0.020% oxygen, 0.001 to 0.030% phosphorus, maximum 0.010% sulphur, maximum 2.0% molybdenum, maximum 2.0% tungsten, balance nickel ≥ 50% nickel and process-related impurities customary for use in solar tower power plants using nitrate melts as heat transfer medium, wherein the following relationship must be met:
[0418] Fp≤39.9 and (2a)
[0419] Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W-11.8*C(3a)
[0420] Wherein Cr, Fe, Al, Si, Ti, Mo, W and C are the concentrations of the relevant elements in mass %.
[0421] 2. The alloy according to technical solution 1, especially used for all parts in contact with molten salt.
[0422] 3. The alloy according to claim 1 or 2, wherein the alloy can be used at a temperature up to 800°C.
[0423] 4. The alloy according to any one of technical solutions 1 to 3, wherein the chromium content is greater than 18% to 33%.
[0424] 5. The alloy according to any one of technical solutions 1 to 4, wherein the aluminum content is 1.8 to 3.8%.
[0425] 6. An alloy according to any one of technical solutions 1 to 5, wherein the iron content is 0.1 to 12.0%.
[0426] 7. The alloy according to one of the technical solutions 1 to 6, wherein the silicon content is 0.001 to <0.40%
[0427] 8. The alloy according to any one of technical solutions 1 to 7, wherein the manganese content is 0.001 to 0.50%.
[0428] 9. The alloy according to any one of technical solutions 1 to 8, wherein the titanium content is 0.001 to 0.50%.
[0429] 10. The alloy according to any one of technical solutions 1 to 9, wherein the carbon content is 0.01 to 0.10%.
[0430] 11. The alloy according to any one of technical solutions 1 to 10, which optionally has an yttrium content of 0.001 to 0.20%.
[0431] 12. The alloy according to any one of claims 1 to 11, optionally having a lanthanum content of 0.001 to 0.20%.
[0432] 13. The alloy according to any one of claims 1 to 12, optionally having a cerium content of 0.001 to 0.20%.
[0433] 14. The alloy according to any one of claims 1 to 13, optionally having a cerium mixed metal content of 0.001 to 0.20%.
[0434] 15. The alloy according to any one of claims 1 to 14, optionally containing 0.0 to 1.1% niobium, wherein formula (3a) is supplemented by a term containing Nb:
[0435] Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.374*Mo+0.538*W-11.8*C(3b) and Cr, Fe, Al, Si, Ti, Nb, Mo, W and C are the concentrations of the relevant elements in mass %.
[0436] 16. The alloy according to any one of claims 1 to 15, optionally having a zirconium content of 0.001 to 0.20%.
[0437] 17. The alloy according to any one of claims 1 to 16, optionally having a hafnium content of 0.001 to 0.20%.
[0438] 18. The alloy according to any one of technical solutions 1 to 17, which optionally has a boron content of 0.0001 to 0.008%.
[0439] 19. The alloy according to any one of technical solutions 1 to 18, which optionally contains 0.0% to 5.0% cobalt.
[0440] 20. The alloy according to any one of claims 1 to 19, further comprising up to 0.5% copper, wherein formula (3a) is supplemented by a term having copper:
[0441] Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.477*Cu+0.374*Mo+0.538*W-11.8*C(3c), and Cr, Fe, Al, Si, Ti, Cu, Mo, W and C are the concentrations of the relevant elements in mass %.
[0442] 21. The alloy according to any one of technical solutions 1 to 20, further containing up to 0.5% vanadium.
[0443] 22. An alloy according to one of technical solutions 1 to 21, wherein the content of the impurities is set to a maximum of 0.002% lead, a maximum of 0.002% zinc, and a maximum of 0.002% tin.
[0444] 23. An alloy according to one of technical solutions 1 to 22, wherein the following formula is satisfied and thus particularly good machinability is achieved: for alloys without Nb, Fa≤60 (4a) and Fa=Cr+20.4*Ti+201*C (5a), where Cr, Ti and C are the concentrations of the relevant elements in mass percentage, or for alloys with Nb, Fa=Cr+6.15*Nb+20.4*Ti+201*C (5b), where Cr, Nb, Ti and C are the concentrations of the relevant elements in mass percentage.
[0445] 24. An alloy according to one of technical solutions 1 to 23, wherein the following formula is satisfied and thus particularly good high temperature strength / creep strength is achieved: for alloys without B and Nb, Fk≥47(6a) and Fk=Cr+19*Ti+10.2*Al+12.5*Si+98*C(7a), where Cr, Ti, Al, Si and C are the concentrations of the relevant elements in mass percentage, or for alloys with B and / or Nb, Fk=Cr+19*Ti+34.3*Nb+10.2*Al+12.5*Si+98*C+2245*B(7b), where Cr, Ti, Nb, Al, Si, C and B are the concentrations of the relevant elements in mass percentage.
[0446] 25. Use of the alloy according to any one of technical solutions 1 to 24 as strips, sheets, wires, bars, longitudinally welded tubes and seamless tubes.
[0447] 26. Use of the alloy according to any one of technical solutions 1 to 24 in the production of strips, sheets, wires, bars, longitudinally welded tubes and seamless tubes.
Claims
1. Nickel-chromium-iron-aluminum alloys having, in mass %, >17 to 33% chromium, 1.8 to <4.0% aluminum, 0.10 to 15.0% iron, 0.001 to 0.50% silicon, 0.001 to 2.0% manganese, 0.00 to 0.60% titanium, 0.0002 to 0.05% magnesium and / or calcium, respectively, 0.005 to 0.12% carbon, 0.001 to 0.050% nitrogen, 0.0001 to 0.020% oxygen, 0.001 to 0.030% phosphorus, max. 0.010% sulfur, max. 2.0% molybdenum, max. 2.0% tungsten, 0.001 to <1.10% Nb, balance nickel with ≥50% nickel, and process-related impurities typical for use in solar tower power plants using nitrate melts as heat transfer medium, wherein the nitrate is a mixture of sodium nitrate and potassium nitrate salts with a composition of 50-70% sodium nitrate and 50-30% potassium nitrate, wherein the following relationship must be met: Fp≤39.9 and (2a) Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+0.374*Mo+0.538*W-11.8*C(3a) Wherein formula (3a) is supplemented by the term of Nb: Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.374*Mo+0.538*W-11.8*C(3b) where Cr, Fe, Al, Si, Ti, Nb, Mo, W and C are the concentrations of the relevant elements in mass %, The alloys described can be used in all components that come into contact with molten salts at temperatures up to 800° C.
2. The alloy according to claim 1, wherein the chromium content is greater than 18% to 33%.
3. The alloy according to claim 1, wherein the aluminum content is 1.8 to 3.8%.
4. The alloy according to claim 1, wherein the iron content is 0.1 to 12.0%.
5. The alloy according to claim 1, wherein the silicon content is 0.001 to <0.40%.
6. The alloy according to claim 1, wherein the manganese content is 0.001 to 0.50%.
7. The alloy according to claim 1, wherein the titanium content is 0.001 to 0.50%.
8. The alloy according to claim 1, wherein the carbon content is 0.01 to 0.10%.
9. The alloy according to claim 1, optionally having an yttrium content of 0.001 to 0.20%.
10. The alloy according to claim 1, optionally having a lanthanum content of 0.001 to 0.20%.
11. The alloy according to claim 1, optionally having a cerium content of 0.001 to 0.20%. 12 . The alloy according to claim 1 , optionally having a cerium mixed metal content of 0.001 to 0.20%.
13. The alloy according to claim 1, optionally having a zirconium content of 0.001 to 0.20%.
14. The alloy according to claim 1, optionally having a hafnium content of 0.001 to 0.20%.
15. The alloy according to claim 1, optionally having a boron content of 0.0001 to 0.008%.
16. The alloy according to any one of claims 1 to 2, optionally containing 0.0% to 5.0% cobalt.
17. The alloy according to claim 1, further comprising up to 0.5% copper, wherein formula (3a) is supplemented by a term for Nb and a term for copper: Fp=Cr+0.272*Fe+2.36*Al+2.22*Si+2.48*Ti+1.26*Nb+0.477*Cu+0.374*Mo+0.538*W-11.8*C(3c), and Cr, Fe, Al, Si, Ti, Cu, Mo, W and C are the concentrations of the relevant elements in mass %.
18. The alloy according to any one of claims 1 to 2, further comprising up to 0.5% vanadium.
19. The alloy according to one of claims 1 to 2, wherein the content of the impurities is set at a maximum of 0.002% lead, a maximum of 0.002% zinc, a maximum of 0.002% tin.
20. The alloy according to claim 1, wherein the following formula is satisfied: Fa≤60 (4a) and Fa=Cr+6.15*Nb+20.4*Ti+201*C (5b), wherein Cr, Nb, Ti and C are the concentrations of the relevant elements in mass percentage.
21. The alloy according to claim 1 , wherein the following formula is satisfied: for alloys with B and / or Nb, Fk ≥ 47 (6a) and Fk = Cr + 19*Ti + 34.3*Nb + 10.2*Al + 12.5*Si + 98*C + 2245*B (7b), wherein Cr, Ti, Nb, Al, Si, C and B are the concentrations of the relevant elements in mass percentage.
22. Use of the alloy according to any one of claims 1 to 2 as strip, sheet, wire, rod, longitudinally welded tube and seamless tube.
23. Use of the alloy according to one of claims 1 to 2 for the production of strips, sheets, wires, bars, longitudinally welded tubes and seamless tubes.
Citation Information
Patent Citations
Nickel-chromium-iron-aluminum alloy with good workability
DE102012002514A1
Nickel-chromium-aluminum alloy with good workability, creep resistance and corrosion resistance
DE102012011161A1
Use of a nickel-chromium-iron-aluminum alloy with good processability
DE102012013437B3
Tube-shaped body made of austenitic steel and solar receiver
DE102015200881A1
heat-resistant nickel-based alloy
DE60004737T2